2018
DOI: 10.1177/0363546518804805
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Femoroacetabular Impingement: A Prospective Study

Abstract: Background: The literature has given little attention to the nonoperative management of femoroacetabular impingement (FAI) syndrome despite a rapidly expanding body of research on the topic. Purpose: To perform a prospective study utilizing a nonoperative protocol on a consecutive series of patients presenting to our clinic with FAI syndrome. Study Design: Cohort study; Level of evidence, 2. Methods: Between 2013 and 2016, patients meeting the following criteria were prospectively recruited in a nonoperative F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 24 publications
1
83
1
2
Order By: Relevance
“…12 Furthermore, inferences can only be made as to the early effectiveness of FAI treatment for quality of life, pain, and function and do not extend to the potentially prophylactic effects on the development of hip arthritis associated with radiographic features of FAI. 13 There is also evidence that patients with labral tears and FAI can be successfully managed with physical therapy, pain management, and activity modification, in combination with intra-articular injections: In a prospective study by Pennock et al, 14 76 of 93 adolescents (82%) with FAI syndrome were successfully managed nonoperatively at a mean follow-up of 2 years. Although the osseous structures involved in FAI are thought to cause pain through bony impingement, studies have also shown that soft-tissue (weakened hip flexors, external rotators, and hip abductors 15,16 ) and biomechanical contributors (abnormalities in gait biomechanics, pelvic obliquity, and pelvic tilt 15,[17][18][19][20][21][22][23] ) lead to increased loading of the acetabular labrum and pain mechanisms.…”
Section: See Commentary On Page 274mentioning
confidence: 99%
“…12 Furthermore, inferences can only be made as to the early effectiveness of FAI treatment for quality of life, pain, and function and do not extend to the potentially prophylactic effects on the development of hip arthritis associated with radiographic features of FAI. 13 There is also evidence that patients with labral tears and FAI can be successfully managed with physical therapy, pain management, and activity modification, in combination with intra-articular injections: In a prospective study by Pennock et al, 14 76 of 93 adolescents (82%) with FAI syndrome were successfully managed nonoperatively at a mean follow-up of 2 years. Although the osseous structures involved in FAI are thought to cause pain through bony impingement, studies have also shown that soft-tissue (weakened hip flexors, external rotators, and hip abductors 15,16 ) and biomechanical contributors (abnormalities in gait biomechanics, pelvic obliquity, and pelvic tilt 15,[17][18][19][20][21][22][23] ) lead to increased loading of the acetabular labrum and pain mechanisms.…”
Section: See Commentary On Page 274mentioning
confidence: 99%
“…Surgery to correct the bony alignment and repair or resect the damaged acetabular labrum has been advocated, with good outcomes reported postoperatively (Kemp et al, ; Kierkegaard et al, ) although recent research has indicated that function and participation in sport and physical activity is still reduced 1 year after surgery (Thorborg et al, ). More recently, conservative nonsurgical management approaches focusing on improving neuromuscular function around the hip have been proposed as an alternative (Casartelli et al, ; Casartelli et al, ; Casartelli et al, ; Pennock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies on conservative treatment for patients with acetabular labral tears and FAI have been reported [9][10][11]. However, the diagnostic accuracy of acetabular labral tear was relatively low in most studies because the diagnosis of labral tear was only dependent on bone morphology and anterior impingement test.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the conservative therapy, however, there is no consensus on the usefulness of physiotherapy to treat acetabular labral tears. Previous studies reported that physiotherapy can improve clinical symptoms [9][10][11], but outcome scores of conservative treatments have been reported to have no difference or to be signi cantly lower than those of arthroscopic surgery [12,13].…”
Section: Introductionmentioning
confidence: 99%